Awareness and Practices for Infection Control Measures in Nurses Working in Intensive Care Unit - Ashiq, Sobia; Liaqat, Javeria; Liaqat, Maria; Nouman, Adeel (Biological and Clinical Sciences Research Journal, 2025)
Infection control in intensive care units (ICUs) is critical to reducing nosocomial infections, morbidity, and mortality. Nurses play a pivotal role in implementing infection control practices; thus, assessing their knowledge and practices is essential to guide targeted interventions. Objective: To evaluate the level of knowledge and practices related to infection control among intensive care unit nurses. Methods: This descriptive prospective study was conducted at the Intensive Care Unit of Medi Care Hospital, Multan, from January 2024 to January 2025. A total of 100 nurses, involved in direct patient care, were included through convenience sampling. Data collection utilised a structured questionnaire and a performance observational checklist. The questionnaire assessed demographic information and infection control protocols, while the checklist evaluated infection control practices across 13 dimensions comprising 95 items. Each nurse was observed during three different procedural occasions and routine duties. Data were analysed using SPSS version 20, and results were presented as means ± standard deviations and percentages. Results: The mean total knowledge score was 111.5 ± 16.7, with only 35% of nurses demonstrating a satisfactory level of knowledge. Deficiencies were noted in knowledge regarding isolation procedures (90%), nosocomial infections (75%), sterilisation techniques (90%), and blood-transmitted diseases (77%). The mean unsatisfactory knowledge score was 101.4 ± 14.2. For practices, the mean score was 70.8 ± 8.6, with 58% of nurses displaying satisfactory practices. Strengths were observed in chest tube care (78%), catheter care (90%), personal hygiene (80%), and endotracheal suctioning (89%). The mean satisfactory practice score was 78.1 ± 4.7. Conclusion: Although ICU nurses demonstrated a satisfactory level of infection control practices, their knowledge was found to be suboptimal. This underscores the necessity for regular training programs and continuing education initiatives targeting all age groups to enhance infection control knowledge and ultimately improve patient outcomes.